Living The Mystery of Communion of the Trinity in The Community - Pham, Van Phong (Khoa Học Công Giáo và Đời Sống, 2022)
The purpose of this article is to provide a comprehensive overview of the mystery of Trinitarian communion before highlighting its applications in the life of the religious community or in the lives of Christians, depending on the condition of life of the reader.